Method in Kelsen’s Pure Theory of Law in dialog with Kant, Neokantianism, and Modernity - Herszenbaun, Miguel (Con-Textos Kantianos. International Journal of Philosophy, 2023)
In this paper, I intend to study Kelsen’s method in the Pure Theory of Law. The aim is to consider its method as a central element in clarifying Kelsen's philosophical affiliation –particularly his relation to Kant, neo-Kantianism, and the modern tradition–, and, through this, to understand main aspects of his philosophical program. I argue that Kelsen’s method explains tensions in his system. The use of the transcendental and synthetic methods (or conceptual analysis) is incompatible with the dynamic study of Law and thus involve an unbridgeable tension between statics and dynamics and validity and efficacy. Thus, I will argue that the aforementioned tension is due to a method that can only be used in the static sphere and whose results are contradicted by the conclusions obtained in the dynamic sphere